MARKETING APPROACHES TO CUSTOMER EXPERIENCE MEASUREMENT AND EVALUATION - A. Serzhantov (Publishing House of the State University of Management, 2017)
The article shows the variety of existing marketing methods to measure and evaluate the consumer experience. The necessity of creation of a comprehensive Customer Experience Management System on the basis of empirical data in order to create a platform for building long-term relationships with customers is proved.